A comprehensive immunohistochemical analysis of 26 markers in 250 cases of serous ovarian tumors - Němejcová, Kristýna; Šafanda, Adam; Bártů, Michaela Kendall; Michálková, Romana; Drozenová, Jana; Fabian, Pavel; Hausnerová, Jitka; Laco, Jan; Matěj, Radoslav; Méhes, Gábor; Škapa, Petr; Stružinská, Ivana; et al. (Diagnostic pathology, 2023)
BACKGROUND: We examined a large cohort of serous tubo-ovarian tumors with 26 immunohistochemical markers, with the aim to assess their value for differential diagnosis and prognosis. METHODS: Immunohistochemical analyses with 26 immunomarkers were performed on 250 primary tubo-ovarian tumors including 114 high grade serous carcinomas (HGSC), 97 low grade serous carcinomas (LGSC), and 39 serous borderline tumors (micropapillary variant, mSBT). The associations of overall positivity with clinicopathological characteristics were evaluated using the chi-squared test or Fisher's Exact test. RESULTS: We found significantly different expression of p53, p16, ER, PR, PTEN, PAX2, Mammaglobin, RB1, Cyclin E1, stathmin, LMP2, L1CAM, CD44, and Ki67 in HGSCs compared to LGSCs. No significant differences were found between LGSC and mSBT. None of the other included markers (PAX8, ARID1A, HNF1B, Napsin A, CDX2, SATB2, MUC4, BRG1, AMACR, TTF1, BCOR, NTRK) showed any differences between the investigated serous tumors. Regarding the prognosis, only PR and stathmin showed a statistically significant prognostic meaning in LGSCs, with better overall survival (OS) and recurrence-free survival (RFS) in cases positive for PR, and worse outcome (RFS) for stathmin. None of the study markers showed prognostic significance in HGSCs. CONCLUSION: We provided an extensive immunohistochemical analysis of serous ovarian/tubo-ovarian tumors. Although we found some differences in the expression of some markers in HGSCs compared to LGSCs, only p53, p16, and Ki67 seem to be useful in real diagnostic practice. We also suggested the best discriminative cut-off for Ki67 (10% of positive tumor cells) for distinguishing HGSC from LGSC. We found prognostic significance of PR and stathmin in LGSCs. Moreover, the high expression of stathmin could also be of predictive value in ovarian carcinomas as target-specific anti-stathmin effectors are potential therapeutic targets.
Keywords: nádorový supresorový protein p53; Tubo-ovarian tumors; Immunohistochemistry; Cystadenocarcinoma, Serous; ženské pohlaví; Humans; Tumor Suppressor Protein p53; nádory vaječníků; Low grade serous carcinoma; Female; Ovarian Neoplasms; High grade serous carcinoma; Ki-67 Antigen; antigen Ki-67; lidé; serózní cystadenokarcinom; Ovarian tumors